NMMD: Efficient Cryo-EM Flexible Fitting Based on Simultaneous Normal Mode and Molecular Dynamics atomic displacements - Vuillemot, Rémi; Miyashita, Osamu; Tama, Florence; Rouiller, Isabelle; Jonic, Slavica (Journal of molecular biology, 2022)
[Display omitted] •NMMD: new method for flexible fitting of atomic structures into cryo-EM maps.•NMMD efficiently combines normal mode analysis and molecular dynamics simulation.•NMMD was tested using synthetic and experimental cryo-EM maps.•Adding normal modes to molecular dynamics makes the fitting faster and more accurate. Atomic models of cryo electron microscopy (cryo-EM) maps of biomolecular conformations are often obtained by flexible fitting of the maps with available atomic structures of other conformations (e.g., obtained by X-ray crystallography). This article presents a new flexible fitting method, NMMD, which combines normal mode analysis (NMA) and molecular dynamics simulation (MD). Given an atomic structure and a cryo-EM map to fit, NMMD simultaneously estimates global atomic displacements based on NMA and local displacements based on MD. NMMD was implemented by modifying EMfit, a flexible fitting method using MD only, in GENESIS 1.4. As EMfit, NMMD can be run with replica exchange umbrella sampling procedure. The new method was tested using a variety of EM maps (synthetic and experimental, with different noise levels and resolutions). The results of the tests show that adding normal modes to MD-based fitting makes the fitting faster (40% in average) and, in the majority of cases, more accurate.